Glosa do wyroku Naczelnego Sądu Administracyjnego z dnia 19 lipca 2016 r., II OSK 2762/14 - Klat-Górska, Elżbieta; Nikiforów, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The study presents the judgment of the Supreme Administrative Court of 19 July 2016, II OSK 2762/14, and acceds to the position of the Court. It was explained that on the grounds of the judgment commented, reference is made to the two essentials of general procedural issues, pointing — first — on the eligibility criteria letters sent by the administration to the applicant, and secondly — the basis to force the administration authority issuing the required procedural act. It was pointed out that regardless of whether the administrative authority violates the interests of action, or silence or protraction, an entity shall find a specific remedy standardized by the legislature (appeal, complaint, complaint for failure to act, the complaint to the court, etc.). It is, therefore, a authority whose essence and, at the same time, the function is tailored to the specific situation of the process
Keywords: Naczelny Sąd Administracyjny; orzecznictwo administracyjne; postępowania administracyjne; glosa; prawo